OPEN MARKETS, FINANCIAL SECTOR DEVELOPMENT AND ECONOMIC GROWTH IN NIGERIA - Kolawole, Bashir Olayinka (European Scientific Journal, ESJ, 2012)
This paper examines the causal linkage between open markets (OPM), financial sector development (FSD) and economic growth in Nigeria. Time series data for the period 1990 to 2010 were fitted into the regression equation using various econometric techniques such as Augmented Dickey Fuller (ADF) test, Granger causality test, Johansen co-integration test and Vector Error Correction Method (VECM). Empirical results reveal that causality does not exist between open markets, financial sector development, and growth as pairwise causation between these variables was also found to be weak and insignificant in the country.